2021
DOI: 10.13189/azb.2021.090201
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Action and Biopreservation by Autochthonous Lactic Acid Bacteria of Fish

Abstract: The purpose of this research was to assess native Lactic Acid Bacteria (LAB) for antimicrobial activities in relation to fish preservation. LAB were isolated from intestine of Oreochromis sp. Listeria monocytogenes, being a big microbial hazard of fresh as well as preserved fish food, was chosen against LAB antimicrobials. In the present study sixteen LAB like isolates from fish intestine were judged for their anti-listeria activities by agar well diffusion assay. Thirteen of them were antagonized Listeria mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…(a) To eliminate the effect of organic acids, pH of the filtered CFS was changed using 1(M) NaOH solution (Udhayashree et al, 2012;Rammelsberg and Radler, 1990;Sanyal and Chatterjee, 2021) and then inhibitory activity of that alkaline CFS (ACFS, pH 7.5) was analyzed against the indicator strains by standard well diffusion method.…”
Section: Prohibitory Activity Of Differently Treated Cfsmentioning
confidence: 99%
See 2 more Smart Citations
“…(a) To eliminate the effect of organic acids, pH of the filtered CFS was changed using 1(M) NaOH solution (Udhayashree et al, 2012;Rammelsberg and Radler, 1990;Sanyal and Chatterjee, 2021) and then inhibitory activity of that alkaline CFS (ACFS, pH 7.5) was analyzed against the indicator strains by standard well diffusion method.…”
Section: Prohibitory Activity Of Differently Treated Cfsmentioning
confidence: 99%
“…(b) The alkaline CFS was treated with catalase (2 mg/ml) (ACCFS) (Jini et al, 2011;Sanyal and Chatterjee, 2021) and evaluated further for antimicrobial activity to get rid of the effect of H2O2.…”
Section: Prohibitory Activity Of Differently Treated Cfsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, sixteen LAB were isolated from the intestine of Oreochromis spp. and investigated for their anti-listeria activity [145]. Among the sixteen isolates, thirteen isolates showed an inhibitory zone on the agar plate inoculated with Listeria monocytogens.…”
Section: Other Metabolitesmentioning
confidence: 99%
“…Furthermore, these microbial isolates were tested in their different forms, including live cells, cell-free supernatant (CFS), alkaline CFS, and heated CFS against L. monocytogens. The results indicated that anti-listeria activities occurred by both heat-stable and sensitive compounds, as well as in live cells [145]. Wiernasz et al [16] investigated six different LAB cultures for the biopreservation of salmon gravlax during 25 days of storage at 8 • C using vacuum packaging.…”
Section: Other Metabolitesmentioning
confidence: 99%